Colorful Treasure From Agro-Industrial Wastes: A Sustainable Chassis for Microbial Pigment Production - Grewal, Jasneet; Woła̧cewicz, Mikołaj; Pyter, Weronika; Joshi, Namrata; Drewniak, Lukasz; Pranaw, Kumar (Frontiers in Microbiology, 2022)
Colors with their attractive appeal have been an integral part of human lives and the easy cascade of chemical catalysis enables fast, bulk production of these synthetic colorants with low costs. However, the resulting hazardous impacts on the environment and human health has stimulated an interest in natural pigments as a safe and ecologically clean alternative. Amidst sources of natural producers, the microbes with their diversity, ease of all-season production and peculiar bioactivities are attractive entities for industrial production of these marketable natural colorants. Further, in line with circular bioeconomy and environmentally clean technologies, the use of agro-industrial wastes as feedstocks for carrying out the microbial transformations paves way for sustainable and cost-effective production of these valuable secondary metabolites with simultaneous waste management. The present review aims to comprehensively cover the current green workflow of microbial colorant production by encompassing the potency of waste feedstocks and fermentation technologies. The commercially important pigments viz. astaxanthin, prodigiosin, canthaxanthin, lycopene and β-carotene produced by native and engineered bacterial, fungal or yeast strains have been elaborately discussed with their versatile applications in food, pharmaceuticals, textiles, cosmetics etc. The limitations and their economic viability to meet the future market demands have been envisaged. The most recent advances in various molecular approaches to develop engineered microbiological systems for enhanced pigment production have been included to provide new perspectives to this burgeoning field of research.